2016
DOI: 10.1002/j.0022-0337.2016.80.6.tb06126.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of an Electronic Clinical Formative Assessment: Dental Faculty and Student Perspectives

Abstract: A traditional summative grading structure, used at Indiana University School of Dentistry (IUSD) for more than 30 years, was identified by faculty as outdated for assessing students' clinical performance. In an effort to change the status quo, a feedback-driven assessment was implemented in 2012 to provide a constructive assessment tool acceptable to both faculty and students. Building on the successful non-graded clinical evaluation employed at Baylor College of Dentistry, IUSD implemented a streamlined elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As each new faculty member was hired, he or she was required to participate in a day‐long orientation that included meeting the administrative deans or departmental chairs to discuss job expectations, a tour of the facility, a human resources presentation to discuss credentialing, and an introduction to IUSD's electronic health record system (axiUm). Additionally, new faculty members attended a formalized two‐hour presentation about the comprehensive care clinics, the teaching of clinical policies and procedures, and the training and evaluation of students using IUSD's formative assessment system 12 . During this presentation, the new faculty members received teaching materials and instructional resources.…”
Section: Methodsmentioning
confidence: 99%
“…As each new faculty member was hired, he or she was required to participate in a day‐long orientation that included meeting the administrative deans or departmental chairs to discuss job expectations, a tour of the facility, a human resources presentation to discuss credentialing, and an introduction to IUSD's electronic health record system (axiUm). Additionally, new faculty members attended a formalized two‐hour presentation about the comprehensive care clinics, the teaching of clinical policies and procedures, and the training and evaluation of students using IUSD's formative assessment system 12 . During this presentation, the new faculty members received teaching materials and instructional resources.…”
Section: Methodsmentioning
confidence: 99%
“…All dental schools have their preclinical students acquire incremental skills with procedures and classroom didactics, but beyond those common traits, we found that assessments of mastery of preclinical skills and knowledge varied from school to school. Of some concern, we found that many schools used OSCEs and typodont‐based exams, despite studies finding those forms of assessment had weak predictive and correlation values for determining clinical competence 6,7,24,25 . One study found that grading in summative assessments was inflated by the instructors’ perspective, possibly due to lack of calibration or to avoid negative interactions with students 25 …”
Section: Discussionmentioning
confidence: 92%
“…There has been an effort in medical and dental education recently to go beyond the status quo to improve formative assessments and student feedback to enhance student learning 12,15,16,21,24,26 . Progress Survey Systems, Formative Feedback Models, Non‐Grading Clinical Assessment Programs, EPAs, and Structured Clinical Exercises have all been formative assessments developed in the last few years to address student learning, feedback, and preparedness 21,24,26,27 . EPAs have shown benefits in medical education as formative milestones that lead to better competency assessment of surgeons, which may resonate with dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches of formative assessment have been reported to improve dental students’ performance on other aspects of dental education, including the structured clinical operative test (SCOT), tutor assessment following problem-based learning, online formative assessment via online exam questions, mini-objective structured clinical examination (mini-OSCE), direct observation of procedural skills (DOPS), and competency-based formative progress assessment system [ 12 – 17 ]. Another new approach that has been attempted and well-received by schools includes a streamlined electronic formative feedback model (FFM) developed by Indiana University School of Dentistry (IUSD) [ 18 ]. Multisource feedback from colleagues and patients had been reported to be well-accepted by dental postgraduate students as an effective formative assessment tool to improve on professionalism [ 19 ].…”
Section: Discussionmentioning
confidence: 99%